2007
DOI: 10.1021/ar700025k
|View full text |Cite
|
Sign up to set email alerts
|

Ionothermal Synthesis of Zeolites, Metal–Organic Frameworks, and Inorganic–Organic Hybrids

Abstract: Ionothermal synthesis, the use of ionic liquids as both solvent and template (structure-directing agent), has been used to prepare zeolites and inorganic-organic hybrids such as metal-organic frameworks. The underlying properties of the ionothermal method are discussed, and it is compared with traditional hydrothermal preparative methods. The materials resulting from ionothermal synthesis are described, and any structural features that can be related to the ionic liquid used as the solvent are discussed. Futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
538
0
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 843 publications
(547 citation statements)
references
References 73 publications
4
538
0
5
Order By: Relevance
“…The group of Morris has recently presented the synthesis of zeolites and other microporous materials in ionothermal media [81][82][83][84], and a complete review on this topic can be found in [85]. It is presented that the ionic liquids can play a double role, as solvent and as SDA.…”
Section: Role Of Structure Directing Agentsmentioning
confidence: 99%
“…The group of Morris has recently presented the synthesis of zeolites and other microporous materials in ionothermal media [81][82][83][84], and a complete review on this topic can be found in [85]. It is presented that the ionic liquids can play a double role, as solvent and as SDA.…”
Section: Role Of Structure Directing Agentsmentioning
confidence: 99%
“…It brings more opportunities to synthesize new compounds [16,17]. Moreover, the ionothermal condition tends to generate interrupted structures, which may be helpful to the formation of extra-large pore openings.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless microemulsion synthesis [80] is also a typical method and interesting alternatives are being used based on environmental-friendly synthetic routes: ionothermal [81], microwave, ultrasound-assisted, and sonochemical synthesis [21,25,28], as well as mechanochemistry [82,83]. The synthesis of this type of compounds has been reviewed several times [63,84,85] and therefore only brief details on each technique are presented herein.…”
Section: Synthesismentioning
confidence: 99%
“…These solvents act both as solvents and templates to avoid the competition interactions between the solvent framework and the template framework that are present in the solvothermal methods [63,81].…”
Section: Synthesismentioning
confidence: 99%